If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0 = 2(4 + 9w) 0 = (4 * 2 + 9w * 2) 0 = (8 + 18w) Solving 0 = 8 + 18w Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '-18w' to each side of the equation. 0 + -18w = 8 + 18w + -18w Remove the zero: -18w = 8 + 18w + -18w Combine like terms: 18w + -18w = 0 -18w = 8 + 0 -18w = 8 Divide each side by '-18'. w = -0.4444444444 Simplifying w = -0.4444444444
| 100x-2x^2=700 | | -10=6x-6 | | x-0.3333333x=54 | | -3x-10=6-5(x-4) | | 4x^2-27x+6=-6+1 | | 4(+1x)=-24 | | 4*x-2y=0 | | 30=8f | | 4(2x-8)=9x-19 | | 2x+1-90=0 | | 3=9x+6 | | 42-8x= | | 2(x-6)=40-5x | | -4x-1+3=-10 | | .5*35(x-8)=595 | | 35=7g | | y=-3*2+8 | | -5x+14=11 | | sqrt(16x^2)=y | | -70+42= | | y=-3*1+8 | | y=-3*0+8 | | 4n-9n=35 | | -2(x-8)+3=19 | | x-33.3333336x=54 | | 26=4x-x+5 | | 3x+(3x)=30 | | y=-3*-1+8 | | 2x^3+3x^2-36x+31=0 | | 11x+1=9x+20 | | 6(x-3)-5x=14 | | Y-7-2y=4 |